Free expression and defamation. (11th April 2018) - Berg, Nathan; Kim, Jeong-Yoo
Abstract: An economic rationale for restrictions on free expression is considered. An expresser obtains positive utility from expressing something but it may have damaging effects, which can be measured by its mean squared error, on others. If social losses from expression exceed benefits significantly, restricting expression can improve social welfare. We analyse expression of distorted information and the social welfare consequences of laws that restrict speech according to three standards: whether transmitted information contains falsity, whether false statements are deliberate and whether the expresser intentionally applies a biased filter to selectively express private information. We also show that the anti-defamation law adopting the negligence rule can lead to the socially optimal level of expression by adjusting the due care standard appropriately.